VIDEO MEDIA PEMBELAJARAN PERAWATAN LUKA ULKUS DIABETES MELLITUS - Suwaryo, Putra Agina Widyaswara; Kristianto, Heri (LPPM STIKES MUHAMMADIYAH GOMBONG, 2015)
The learning process is very important to distribute or transfer the knowledge of the teachers or lecturers to students. The application requires a sample or samples of nursing actions, for example the theory that describes the treatment of wounds it will be understood when it is accompanied by a video that is directly applicable wound care performed by nurses to patients (real and the method can play a role). So there needs to be a solution or alternative to solve the problem.Method of product design; instructional media, which produces video instructional media. Video media that has been created contains ulcer wound care diabetes mellitus duration of 25 minutes 37 seconds. Video content on the reviews wound ulcer diabetes mellitus, causes, the occurrence of injury, investigation and physical examination needs to be done to determine the diagnosis or problem.Â Keywords: Video instructional media, ulcer wound care